Systematic choice of video game benchmarks in Deep Reinforcement Learning - Gomes, Élvio; Souza, Marlo (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
Deep Reinforcement Learning has gained much attention due to results obtained by its methods to problems of high dimensionality, which were previously intractable or difficult to solve. In this context, video games have been widely used as experimental environments and benchmarks for the evaluation of reinforcement learning algorithms, as well as guiding the development of new methods. Although a lot has been done in Deep Reinforcement Learning since the proposal of its seminal work, little has been discussed about proper methodologies for constructing such evaluation benchmarks. This paper proposes to systematize the choice of video games to be used as a benchmark guaranteeing representativeness and diversity of learning environments based on the use of video game typologies proposed in the area of Game Design Research.